PwC's Sports Survey 2017 (PwC, 2017)
This survey was conducted between the months of May and June 2017 through an online questionnaire that was sent to a wide variety of sports industry stakeholders. In particular, we received the support of the European Broadcast Union (EBU), the European Professional Football Leagues (EPFL) and the European Club Association (ECA), each of which reached out to their respective members on our behalf. In total, we received 189 complete responses to our questionnaire. iSportconnect also provided support by sending the questionnaire to a selection of their contacts. At the time of their responses, each of the respondents occupied a senior/ C-level position within their respective organisations. The analysis within this report is based on the collective opinion of the respondents.